On a new Ercolania Trinchese, 1872 (Opisthobranchia, Sacoglossa, Limapontiidae) living within Boergesenia Feldmann, 1950 (Cladophorales), with notes on anatomy, histology and biology - Grzymbowski, Yvonne; Stemmer, Kristina; Wägele, Heike (Zootaxa, 2007)
A new sacoglossan species, belonging to the genus Ercolania Trinchese, 1872 is described. E. kencolesi sp. nov. has a similar biology as E. endophytophaga Jensen, 1999. Both are living within syncytial algal tubes of members of the Siphonocladales, E. kencolesi sp. nov. in Boergesenia forbesii and E. endophytophaga in Struvea plumosa. Assignment to the genus Ercolania is possible on the base of the cerata, which are round in cross-section, the digitiform rhinophores, sabot-shaped teeth and the presence of a penial stylet. The new species can be easily distinguished from E. endophyto-phaga, by the teeth with a prominent cusp, as well as other Ercolania species, by its unique colouration and its peculiar association to the food alga Boergesenia. Feeding, copulation, egg masses and development are noted. Differences in development further strengthen the distinction of E. kencolesi to E. endophytophaga. Measurement of photosynthetic activity of incorporated chloroplasts during several days clearly shows that chloroplasts are digested.